Situation of the inclusion of women and young people in agricultural and rural areas in the Democratic Republic of Congo (DRC) - Yeo, P.A.; Arouna, A.,; Yergo, W.; Mushiya, J.; Lufuluabo, M.M.; Mujawamariya, G. (AfricaRice, 2024)
From 24 to 29 August 2024, data was collected on the situation regarding the inclusion of women and young people in rural agricultural areas in the Democratic Republic of Congo. It is part of the activities to be carried out by the CGIAR TAFS-WCA initiative, including reflections on gender issues and obstacles to the empowerment of vulnerable groups in agricultural value chains. The research approach is qualitative and ethnographic. The surveys covered three cultural areas in North Kivu: the villages of Kibumba/Nyiragongo and Masisi in Goma; Mudaka and Kavumo in Bukavu; and Kamanyola and Luvungi in Uvira. Stakeholder consultations were based on Focus Group Discussions (FGD), small group interviews and semi-structured individual interviews. A total of 106 agricultural stakeholders were interviewed in the selected communities. The data was analysed using an approach that prioritised their opinions. Overall, women farmers in Kivu face major challenges in terms of economic and social inclusion. Local customs tend to discriminate against them. In many areas, women are seen as beings who must remain at the service and under the authority of men. They also find it difficult to gain personal access to the land because of the man's control over this resource. Women in Kivu therefore find it very difficult to be autonomous. Young people are also faced with the challenge of inclusion in the farming communities of North Kivu. Perceived as social cadets, they are generally excluded from resource management. Only their elders manage to develop prosperous production activities thanks to their control over access to land. These conditions discourage many young people from getting involved in farming. Due to a lack of opportunities, some of them are driven to rural exodus or to take winding paths such as enlisting in the ranks of the armed rebel groups occupying the east of the country. This data confirms how the gender inequalities faced by women and young people in rural areas affect their social and economic development.